IMPLEMENTASI POLA PERMAINAN UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI SENAM LANTAI SISWA SMKN 4 GOWA - Anto Sukamto; Retno Farhana Nurulita (EDU RESEARCH, 2023)
The aim of this research is to determine the application of game patterns to improve student learning outcomes at SMKN 4 Gowa on floor exercise material. This research is an example of classroom action research, where cycle I and II test data can be used to measure improvements in student learning outcomes in floor exercise material. With a sample size of 29 students, the research subjects were class X students at SMKN 4 Gowa. Student learning results before the revision showed students' low ability to perform floor exercise movements without using equipment: on average only 51.72% were able to perform floor exercise movements well and correctly. The results of the researcher's observations showed that the teaching and learning process before the improvements were carried out, the average student was only 51.72%, the score criteria was > KKM 80. After undergoing corrective action, in cycles I and II there was an increase. Student learning outcomes were seen on average in cycle I. Students were 75.86% with sufficient criteria, and the average of students in cycle II was 93.10% with "Good" criteria. The object of this research is improving student learning outcomes in floor exercise through game patterns. Based on data analysis, it can be concluded that applying game patterns to floor exercise material without equipment can improve the learning outcomes of class X students at SMKN 4 Gowa. This can be seen from the increase in learning outcomes from cycle I to cycle II, after taking action it reached 75.86% in cycle I, an increase also occurred in cycle II reaching 93.10%.